2021
DOI: 10.1111/nep.13856
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of acute kidney injury in COVID‐19 patients

Abstract: Aim This study aims to determine the frequency of COVID‐19 related AKI and to identify the early predictors of AKI. Methods This study is a single‐center, retrospective, observational study. Hospitalized COVID‐19 patients between 24/03/2020 and 31/05/2020 were included in the study. All patients were evaluated for renal dysfunctions with urine dipstick, protein/creatinine ratio, albumin/creatinine ratio in spot urine, serum cystatin C, serum creatinine level on hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
2
28
0
3
Order By: Relevance
“…Proteinuria and albuminuria were also significantly elevated in COVID-19 patients with later occurrence of AKI, which concurs with the findings of previous studies [ 13 , 14 ]. However, compared to proteinuria and albuminuria, KIM-1 detected subsequent AKI with higher sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 92%
“…Proteinuria and albuminuria were also significantly elevated in COVID-19 patients with later occurrence of AKI, which concurs with the findings of previous studies [ 13 , 14 ]. However, compared to proteinuria and albuminuria, KIM-1 detected subsequent AKI with higher sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 92%
“…We identified the data by searching PubMed and references from relevant articles using the search terms “Coronavirus Disease 2019”, “COVID-19”, “SARS-CoV-2”, “kidney disease”, “acute kidney injury”, “AKI”, “risk factors”, “gender”, “clinical outcomes”, and “Clinical Characteristics”. We found that the SARS-CoV-2 infection rate in males is higher than that in females, and the incidence of AKI in males is also higher than that in females in most studies ( Figures 1 , 2 ) ( Cheng et al., 2020b ; Fisher et al., 2020 ; Hirsch et al., 2020 ; Kolhe et al., 2020 ; Pei et al., 2020 ; Sang et al., 2020 ; Zahid et al., 2020 ; Basalely et al., 2021 ; Chan et al., 2021 ; Cheng et al., 2021 ; Costa et al., 2021 ; Dai et al., 2021 ; Diebold et al., 2021 ; Gasparini et al., 2021 ; Martinez-Rueda et al., 2021 ; Mousavi Movahed et al., 2021 ; Ng et al., 2021 ; Ozturk et al., 2021 ; Russo et al., 2021 ; Xu H. et al., 2021 ; Xu J. et al., 2021 ; Yildirim et al., 2021 ; Zamoner et al., 2021 ). In these studies, all of the patients with COVID-19 had new-onset AKI during hospitalization.…”
Section: Gender Differences In the Incidence Of Aki Among Patients With Covid-19mentioning
confidence: 94%
“…Recently, Cigdem et al found that serum Cystatin C showed a good predictive power for AKI in patients with COVID-19. The AUC value of serum Cystatin C to predict COVID-19 related AKI was 0.96 (0.90 to 1.0), with the best cut-off value of 1.00 mg/L [22]. Albina et al previously investigated the potential of plasma N-terminal prohormone B-type natriuretic peptide (NT-proBNP), mid-regional pro-atrial natriuretic peptide (MR-proANP) and B-type natriuretic peptide (BNP) levels to predict early AKI in hospitalized patients with CAP.…”
Section: Discussionmentioning
confidence: 98%